Role Of Health Agencies In Providing Benzathine Penicillin To Sore Throat Cases - Arya R.K; Gaur S.D; Kumar S (Wolters Kluwer Medknow Publications, 1992)
This study (ICMR collaborative) has been conducted In Chiraigaon Block of Varanasi District, up, between January 1984 and September 1987. Health personnel of the Primary Health Center (PHC), Rural Health Training Center (RHTC) and voluntary Health Agency (VHA) were trained to detect sore throats in children in the age group 5 to 15 years. The average number of sore throat cases detected per effective worker month was 12.3 and 8.3 for PHC and RHTC respectively. Injection Benzathine Penicillin was provided as sledgehammer approach compliance ranged from 97.1% to 100%. This study can be helpful for implementation of the national programme for prevention of the Rheumatic Fever and Rheumatic Heart Disease.